A Mini-Review of Accreting Pulsating White Dwarfs - Szkody, Paula (Frontiers in Astronomy and Space Sciences, 2021)
The discovery in 1998 of a pulsating white dwarf in the cataclysmic variable GW Lib opened up a new avenue of exploration in the asteroseismology of white dwarfs. Since dwarf novae undergo outbursts which heat the white dwarf and then subsequently cool, the temperature changes allow a study of the mode changes that occur as the white dwarf moves out of the instability zone and back. These changes occur on timescales of months-years, instead of the millennia for evolutionary cooling of single white dwarfs. At the current time, there are 18 known accreting white dwarf pulsators. This mini-review will summarize the results that have been achieved so far from coordinated space and ground observations, from sky surveys, and what is needed in the future to make further progress.